Kebijakan Upah Minimum Dan Perlindungan Buruh Pabrik Dalam Perspektif Hukum Dan HAM - Shindy Dwianisa; Sindi Andriyani (GLOBAL SCIENTS PUBLISHER, 2025)
This paper discusses the minimum wage policy and the protection of factory workers from a legal and human rights (HAM) perspective. The legal issue under study is that there are still many companies that pay substandard wages even though the government has set a minimum wage policy, thus causing violations of workers' rights to a decent livelihood. The purpose of this paper is to analyze minimum wage policies within the framework of law and human rights and assess the role of governments and companies in ensuring the protection of factory workers. The research method used is normative legal research with a legislative and conceptual approach, which examines national regulations and international instruments related to labor rights. The results of the study show that the minimum wage is not only an economic instrument, but also part of the human rights protection guaranteed by the constitution and international conventions. However, weak law enforcement and government supervision cause workers to remain vulnerable to exploitation, unearned wages, and lack of access to legal protection. Therefore, it is necessary to strengthen regulations, the effectiveness of supervision, and the seriousness of the government in ensuring real worker protection.